Individual choice of management research agendas: Ethical guidance from Islamic prioritization heuristics. Issue 1 (11th February 2020) - El-Bassiouny, Noha; Amin, Ahmed; Jamal, Ahmad
Abstract : Purpose: The main research attempts guiding questions about management research agendas had been relevance questions versus rigor questions. Researchers have also attempted to set management research agendas in particular sectors. To the best of the authors' knowledge, no research, however, has addressed the infrastructural and foundational questions of what moral priorities and ethical principles should guide the future development of management research. Because the Islamic theological approach is a "transcendental values integration" approach, it presents a potentially viable source of reference particularly for scholars interested in ethical philosophical paradigmatic approaches. Islamic literature has presented guiding principles as to how to balance priorities through the Jurisprudence of Priorities (Fiqh Al-Awlawiyyat). The purpose of this exploratory conceptual paper is to synchronize the Islamic background literature on the jurisprudence of priorities with management research development and agendas. The research is exploratory in nature. Design/methodology/approach: The paper is conceptual, merging Islamic literature with management research for the development of a framework to potentially guide management researchers in prioritizing their research agendas. Findings: The research resulted in the conceptualization of a framework aiding researchers in the prioritization of their research agendas. Research limitations/implications: The research has implications for management scholars who are interested to prioritize their research projects and agendas. The research presents a schematic diagram and guiding framework through which scholars can reflect on their choice of research topics. Practical implications: The research is also relevant to funding agencies as they devise the funding priorities in the management field. Originality/value: This paper addresses the unique and foundational question of what moral priorities and ethical principles should guide the future development of management research. The authors build on a religious-philosophical approach, drawing on the Islamic jurisprudence of priorities as a literature base. The authors, therefore, address the key principles of responsible research regarding how it can be relevant on the infrastructural level to society and how the benefit to key stakeholders should be tackled. To the authors' knowledge, this was not done in previous literature.